Cell-Based Therapies in Vascularized Composite Allotransplantation - Vyas, Krishna S.; Mohan, Anita T.; Morrison, Shane D.; Tran, Duy C.; Mardini, Samir (Journal of Reconstructive Microsurgery, 2018)
Background Dendritic cells (DCs) are bone marrow-derived, professional antigen-presenting cells with tolerogenic function. The ability of DCs to regulate alloantigen-specific T cell responses and to promote tolerance has aligned them ideally for a role in vascularized composite allotransplantation (VCA). In this study, we summarize the current evidence for DC therapies for tolerance induction to alleviate the requirement for chronic immunosuppression.Method A comprehensive and structured review of manuscripts published on VCA was performed using the MEDLINE and PubMed databases. All eligible studies published from the year 2000 to 2017 were included in the final results.Result Nineteen original preclinical and clinical studies that employed cell therapy for VCA were included in this review. In vivo DC therapy was found to direct the alloimmune response toward either transplant rejection or tolerance in VCA models. While injection of mature DCs rapidly increases T-cell activity in humans and promotes transplant rejection, the injection of immature DCs acts as an immunosuppressant and inhibits T-cell activity. In addition to immature DCs, mesenchymal stem cells were also found to have a positive effect on allotransplantation of solid organs and bone marrow via cytokine expression which decreases the alloreactive effector lymphocytes and increases CD4+/CD25+/FoxP3 Tregs. Despite the promising findings, the efficacy of cell-based therapies varies greatly across studies, partly due to different methods of cell isolation and purification techniques, source, route and timing of administration, and combination immunosuppressive therapy.Conclusion Additional research is needed to evaluate the efficacy and safety of DC and other cell-based therapeutic measures in human allotransplant recipients. Future direction will focus on the development of novel methods to reduce immunosuppression and develop more individualized management, as well as the clinical application of basic research in the mechanisms of immunologic tolerance.
Keywords: tolerogenic dendritic cells; dendritic cells; composite tissue allotransplantation; vascularized composite allotransplantation; immunosuppressive; cell-based therapy; immune tolerance; transplantation; immature DCs; DCs